Repression of Sex4 and Like Sex Four2 Orthologs in Potato Increases Tuber Starch Bound Phosphate With Concomitant Alterations in Starch Physical Properties - Samodien, Ebrahim; Jewell, Jonathan F.; Loedolff, Bianke; Oberlander, Kenneth; George, Gavin M.; Zeeman, Samuel C.; Damberger, Fred F.; van der Vyver, Christell; Kossmann, Jens; Lloyd, James R. (Frontiers in Plant Science, 2018)
To examine the roles of starch phosphatases in potatoes, transgenic lines were produced where orthologues of SEX4 and LIKE SEX FOUR2 (LSF2) were repressed using RNAi constructs. Although repression of either SEX4 or LSF2 inhibited leaf starch degradation, it had no effect on cold-induced sweetening in tubers. Starch amounts were unchanged in the tubers, but the amount of phosphate bound to the starch was significantly increased in all the lines, with phosphate bound at the C6 position of the glucosyl units increased in lines repressed in StSEX4 and in the C3 position in lines repressed in StLSF2 expression. This was accompanied by a reduction in starch granule size and an alteration in the constituent glucan chain lengths within the starch molecule, although no obvious alteration in granule morphology was observed. Starch from the transgenic lines contained fewer chains with a degree of polymerization (DP) of less than 17 and more with a DP between 17-38. There were also changes in the physical properties of the starches. Rapid viscoanalysis demonstrated that both the holding strength and the final viscosity of the high phosphate starches were increased indicating that the starches have increased swelling power due to an enhanced capacity for hydration.